The impact of financial solvency and corporate risk management on achieving financial stability: An applied study in the Iraqi insurance market - Noor Ali Salman (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Financial stability is crucial for insurance companies to meet obligations and sustain operations. Specific Background: Insurance companies face various risks, making enterprise risk management and solvency important factors in maintaining stability. Knowledge Gap: Limited evidence exists on the relative contribution of solvency and enterprise risk management to the financial stability of Iraqi insurance companies. Aims: This study examined the roles of solvency and enterprise risk management in the financial stability of two Iraqi insurance companies using the Autoregressive Distributed Lag (ARDL) model. Results: The findings revealed that solvency had no significant effect on financial stability in either the short run or the long run. In contrast, enterprise risk management, represented by the retention ratio, showed a significant positive contribution to long-term financial stability. The error correction term confirmed a stable long-run relationship among the variables. Novelty: The study provides evidence from the Iraqi insurance sector by jointly analyzing solvency and enterprise risk management within a dynamic framework. Implications: The results suggest that financial stability relies more on effective risk management than on capital adequacy alone, emphasizing the importance of sound risk governance in insurance companies. Keywords: Enterprise Risk Management, Financial Stability, Insurance Companies, Solvency, ARDL Model Key Findings HighlightsRisk retention practices were associated with stronger long-term organizational sustainability.Capital adequacy alone was insufficient to explain variations in stability indicators.Equilibrium adjustment mechanisms confirmed persistent relationships among the examined variables.